General aviation security : aircraft, hangars, fixed-base operations, flight schools, and airports - Benny, Daniel J. (CRC Press, 2013)
"This book has been designed and written for the primary purpose of providing a single comprehensive source of information in order to provide for the protection of general aviation aircraft, hangars, fixed base operations, flight schools, and airports. Addressing all aspects of general aviation security, it supplies guidance to organizations such corporate flight departments, general aviation aircraft owners, pilots, flight school and airports"--